Expression of the connections between interlocutors in society within intonation incentives (experimental research) - Elijošiūtė, S. (Psichologija, 1968)
An experimental twenty-six incentive intonation structure investigation demonstrated that according to a series of acoustic features some incentives group into two zones. Juxtaposition of incentives going into opposite zones demonstrated that they are characterized by different the connections between interlocutors in society (in a specific act of communication). Consequently, a number of intonation incentive structure attributes are this communication condition’s indicators within the intonation incentives. This article indicates factors of determining the connections between interlocutors in society (in a specific act of communication) as one of the conditions where there is incentivized communication. This communication condition’s representation in incentives is particularly important in terms of their efficacy. Man, as a social being, really needs public activity, including actions encouraging evaluation.